2009
DOI: 10.1111/j.1439-0426.2009.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the vertical distribution of larval lake sturgeon drift in the Peshtigo River, Wisconsin, USA

Abstract: Drift nets have been used to document reproductive success of lake sturgeon Acipenser fulvescens. Current net designs and methods for collecting drifting larvae only sample a portion of the water column, which require assumptions of either a benthic or uniform distribution of larvae when estimating abundance or production. The objective of this study was to describe the vertical distribution of larval lake sturgeon in the Peshtigo River, Wisconsin, and to determine if drift was benthic or uniform in distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Though efforts and subsequent recoveries have been variable (Caroffino et al 2009a), stocking programs (Chalupnicki et al 2011), dam removal (Dieterman et al 2010), and habitat improvements (Roseman et al 2011) have all led to population improvements. Further, in at least one case a population appears to be recovering naturally (Bauman et al 2011).…”
Section: The Declinementioning
confidence: 99%
“…Though efforts and subsequent recoveries have been variable (Caroffino et al 2009a), stocking programs (Chalupnicki et al 2011), dam removal (Dieterman et al 2010), and habitat improvements (Roseman et al 2011) have all led to population improvements. Further, in at least one case a population appears to be recovering naturally (Bauman et al 2011).…”
Section: The Declinementioning
confidence: 99%
“…This may be a function of flow as the current downstream of a dam is not as dispersed as in a natural river, but turbulence flows with high velocity emanating from turbines or sluice gates. Drifting larvae are surface‐oriented (Caroffino, Daugherty, & Sutton, ; Caroffino et al., ; Verdon et al., ) and could be flushed out of turbulent flows and settle within the first pool (i.e., close to the dam). An alternate theory could be related to the timing of drift associated with the operation of the hydroelectric facility.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is often assumed that sampling just off the bottom at night results in the collection of most of the drifting larvae (Auer and Baker, ), most studies have shown that vertical distribution of larval lake sturgeon varies with the time of day and location. In the Peshtigo River, larvae were captured drifting throughout the water column, but were found nearer to the surface than the bottom (Caroffino et al., ). The authors conclude that sampling only a portion of the water column may preclude the capture of a significant percentage of drifting larvae.…”
Section: Discussionmentioning
confidence: 99%